Laporan latihan praktik di Kolej Teknologi Cosmopoint Cawangan Sungai Petani, Kedah Darul Aman / Mohd Yusof Md. Harris and Muhammad Fahmi Mazlan - Md.Harris, Mohd Yusof; Mazlan, Muhammad Fahmi (Universiti Teknologi MARA, Kedah, 2007)
Cosmopoint Metro Campus Sungai Petani (Cosmo SP), has started its operation in April 1998. Currently, this branch is lead or managed by En.Ahmad Fauzi bin Abdul Jalil as a centre manager and assisted by 34 administration staffs and lecturers. Two shop houses have been used to run the operation of Cosmopoint Metro Campus Sungai Petani and it consists of 3 levels. The students currently enrolled in various diploma and certificate programs consists of all races namely Malay, Chinese and Indian. The students' population until the end of March 2007 is 368 students. Since its establishment, Cosmopoint Metro Campus Sungai Petani has produced 1753 students in various courses. The Cosmopoint Metro Campus Sungai Petani is equipped with a library that has good quality books and journals, counseling room or consultation room, prayer room, computer lab equipped with 211 computers, comfortable lecture hall and tutorial rooms, working lab, LCD projector equipment for lecture session, R&D room for lecturers and also comfortable lecture hall. Its strategic position which is near Sungai Petani bus station is made Cosmopoint Sungai Petani such an attractive learning institution among the students who choose IPTS as their educational institute.